PERAN PEMBELAJARAN ILMU TAJWID DALAM MEMBANGUN KOMPETENSI SPIRITUAL DAN LITERASI QUR’ANI PESERTA DIDIK - Shendya Lukyana Yumna; Fathara Aydalhaqq; Nurul Mubin (JOURNAL SAINS STUDENT RESEARCH, 2025)
Learning Tajweed plays a crucial role in developing students' spiritual competence and Qur'anic literacy. By understanding the rules of Tajweed, students can read the Qur'an correctly and precisely according to the rules of recitation taught by the Prophet Muhammad (peace be upon him), thereby improving the quality of their reading and understanding of the Qur'an's message. Learning Tajweed not only improves reading skills such as tartil, accuracy, and fluency, but also motivates students to continue reading and deepening their understanding of the Qur'an regularly. This has a positive impact on the development of spiritual competence because students are able to internalize the meaning and values ​​of the Qur'an, which strengthen their faith and piety. Therefore, learning Tajweed is an important foundation in building holistic Qur'anic literacy, encompassing both the technical aspects of reading and the spiritual aspects of students as Muslims. Research shows a significant relationship between mastery of Tajweed and improvements in Qur'anic reading skills and students' spiritual motivation.